Patterns of failure after use of 18F-FDG PET/CT in integration of extended-field chemo-IMRT and 3D-brachytherapy plannings for advanced cervical cancers with extensive lymph node metastases. Issue 1 (December 2016) - Chung, Yih-Lin; Horng, Cheng-Fang; Lee, Pei-Ing; Chen, Fong-Lin
Abstract Background The study is to evaluate the patterns of failure, toxicities and long-term outcomes of aggressive treatment using18 F-FDG PET/CT-guided chemoradiation plannings for advanced cervical cancer with extensive nodal extent that has been regarded as a systemic disease. Methods We retrospectively reviewed 72 consecutive patients with18 F-FDG PET/CT-detected widespread pelvic, para-aortic and/or supraclavicular lymph nodes treated with curative-intent PET-guided cisplatin-based extended-field dose-escalating intensity-modulated radiotherapy (IMRT) and adaptive high-dose-rate intracavitary 3D-brachytherapy between 2002 and 2010. The failure sites were specifically localized by comparing recurrences on fusion of post-therapy recurrent18 F-FDG PET/CT scans to the initial PET-guided radiation plannings for IMRT and brachytherapy. Results The median follow-up time for the 72 patients was 66 months (range, 3–142 months). The 5-year disease-free survival rate calculated by the Kaplan-Meier method for the patients with extensive N1 disease with the uppermost PET-positive pelvic-only nodes (26 patients), and the patients with M1 disease with the uppermost PET-positive para-aortic (31 patients) or supraclavicular (15 patients) nodes was 78.5 %, and 41.8–50 %, respectively (N1 vs. M1, p = 0.0465). Eight (11.1 %), 18 (25.0 %), and 3 (4.2 %) of the patients developed in-field recurrence, out-of-field and/or distant metastasis, and combined failure, respectively. The 6 (8.3 %) local failures around the uterine cervix were all at the junction between IMRT and brachytherapy in the parametrium. The rate of late grade 3/4 bladder and bowel toxicities was 4.2 and 9.7 %, respectively. When compared to conventional pelvic chemoradiation/2D-brachytherapy during 1990–2001, the adoption of18 F-FDG PET-guided extended-field dose-escalating chemoradiation plannings in IMRT and 3D-brachytherapy after 2002 appeared to provide higher disease-free and overall survival rates with acceptable toxicities in advanced cervical cancer patients. Conclusions For AJCC stage M1 cervical cancer with supraclavicular lymph node metastases, curability can be achieved in the era of PET and chemo-IMRT. However, the main pattern of failure is still out-of-field and/or distant metastasis. In addition to improving systemic treatment, how to optimize and integrate the junctional doses between IMRT and 3D-brachytherapy in PET-guided plannings to further decrease local recurrence warrants investigation.